2009
DOI: 10.1016/j.neuro.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of delta-aminolevulinic acid dehydratase (ALAD) and peptide transporter 2 (PEPT2) genes in children with low-level lead exposure

Abstract: Low-level lead exposure during early childhood has long been associated with altered neurocognitive development and diminished cognitive functions. Over nine thousand U.S. industrial facilities annually emit significant amounts of lead, creating exposure risk particularly for minority children. The mechanisms by which low-level lead exerts neurotoxic effects are poorly understood. Once absorbed, the only intervention is source removal, thus primary prevention is key. Genetic biomarkers could provide an efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Similarly, in 229 children in China, mean BLL was higher in children with ALAD 2 (11.7 µg/dL vs. 9.7 µg/dL) (Shen et al, 2001). Associations were also observed at lowest levels of exposure in young children (Sobin et al, 2009), and when gender effects were examined differences were found (Sobin et al, 2011b). As compared to other subgroups, mean BLL was highest among males with ALAD 2 [ID: rs1800435] (3.5 µg/dL vs. 2.7 µg/dL).…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, in 229 children in China, mean BLL was higher in children with ALAD 2 (11.7 µg/dL vs. 9.7 µg/dL) (Shen et al, 2001). Associations were also observed at lowest levels of exposure in young children (Sobin et al, 2009), and when gender effects were examined differences were found (Sobin et al, 2011b). As compared to other subgroups, mean BLL was highest among males with ALAD 2 [ID: rs1800435] (3.5 µg/dL vs. 2.7 µg/dL).…”
Section: Introductionmentioning
confidence: 94%
“…The variants, expressed in Chinese hamster ovary cells, displayed similar V max values for GlySar uptake but a 3-fold higher K m value in hPEPT2 * 2 (i.e., 233 µM vs. 83 µM in hPEPT2 * 1 ). Children homozygous for the hPEPT2 * 2 polymorphism had higher blood levels of lead than children with the hPEPT2 * 1 variant (Sobin et al , 2009), suggesting an increased risk of 5-ALA-induced neurotoxicity for this population. Finally, another variant, Arg57His, had a complete loss of transport function when transfected in HEK293 cells and Xenopus oocytes (Terada et al , 2004), although the frequency of this single nucleotide polymorphism was considered rare.…”
Section: Discussionmentioning
confidence: 91%
“…Shaik and Jamil (32) reported that blood lead levels did not differ significantly among ALAD1-1, 1-2 and 2-2 genotypes. Additionally, Sobin et al (33) reported that there was no association between ALAD2 and sub-clinical blood lead burden.…”
Section: Primary Brain Tumormentioning
confidence: 99%